Simulation of piston secondary motion within power cylinder units - Hansson, Mathias; Hermansson, Adam (My University, 2017)
This master’s thesis concerns the development of a methodology for simulation of piston secondary motion. Firstly, a procedure for performing simulations in a newly developed software is proposed. Secondly, simulations for two particular pistons are carried out to analyze piston secondary motion, piston skirt friction, hydrodynamic pressure in the lubrication oil between the piston and the cylinder liner, the deformation of the piston skirts, and the lubrication oil distribution within a power cylinder unit. The efficiency and robustness of the proposed procedure is illustrated in the simulations of the two pistons. The results show that the software can become a powerful tool when predicting the behavior of pistons inside a power cylinder unit, by comparing the results to real measurements. Furthermore, another goal was to give valuable feedback to the developer to aid the continued work with the software.
Keywords: Teknisk mekanik; Applied Mechanics